2015
DOI: 10.1186/s40001-015-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

Biliary tract external drainage increases the expression levels of heme oxygenase-1 in rat livers

Abstract: BackgroundHeme oxygenase-1 (HO-1) protects cells by anti-oxidation, maintaining normal microcirculation and anti-inflammatory under stress. This study investigated the effects of biliary tract external drainage (BTED) on the expression levels of HO-1 in rat livers.MethodsBiliary tract external drainage was performed by inserting a cannula into the bile duct. Sixty Sprague–Dawley rats were randomized to the following groups: sham 1 h group; BTED 1 h group; bile duct ligation (BDL) 1 h group; sham 6 h group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…HO-1 is a stress-inducible enzyme which catalyzes the degradation of heme into CO, iron and biliverdin [ 7 ]. Under oxidative stress, such as inflammation and ischemia-reperfusion, HO-1 is induced and protects organs from damage, which in part by the anti-inflammatory effect of heme metabolites [ 31 35 ]. The expression of genes responsible for oxidative stress, especially HO-1 [ 16 , 36 , 37 ], are remarkably upregulated in the course of SAP, which suggests the existence of a compensatory mechanism against stress.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is a stress-inducible enzyme which catalyzes the degradation of heme into CO, iron and biliverdin [ 7 ]. Under oxidative stress, such as inflammation and ischemia-reperfusion, HO-1 is induced and protects organs from damage, which in part by the anti-inflammatory effect of heme metabolites [ 31 35 ]. The expression of genes responsible for oxidative stress, especially HO-1 [ 16 , 36 , 37 ], are remarkably upregulated in the course of SAP, which suggests the existence of a compensatory mechanism against stress.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is an enzyme that regulates the breakdown of heme to biliverdin, iron, and CO. 34 It was reported that HO-1 may be beneficial as it ameliorated the negative effects of oxidative stress, and hence protects organs, partly by suppressing inflammation induced by heme metabolites. 9,10,[35][36][37] In this way, HO-1 protects organs from inflammation-induced injury and oxidative stress. We previously showed that HO-1 protected the pancreas from injury during SAP by inhibiting TNFa and enhancing IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…As the technology becomes more minimally invasive, biliary tract external drainage (BTED) is widely applied in critically ill patients, such as severe acute pancreatitis, malignant biliary obstruction (5)(6)(7), acute cholangitis (8)(9)(10)(11). In our previous studies, BTED decreased multiorgan dysfunction in HS by affecting enterohepatic circulation of bile pigments (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%